The role of intolerance of uncertainty in classical threat conditioning: Recent developments and directions for future research - Morriss, Jayne; Zuj, Daniel V.; Mertens, Gaëtan (International journal of psychophysiology, 2021)
Intolerance of uncertainty (IU), the tendency to find uncertainty aversive, is an important transdiagnostic dimension in mental health disorders. Over the last decade, there has been a surge of research on the role of IU in classical threat conditioning procedures, which serve as analogues to the development, treatment, and relapse of anxiety, obsessive-compulsive, and trauma- and stressor-related disorders. This review provides an overview of the existing literature on IU in classical threat conditioning procedures. The review integrates findings based on the shared or discrete parameters of uncertainty embedded within classical threat conditioning procedures. Under periods of unexpected uncertainty, where threat and safety contingencies change, high IU, over other self-reported measures of anxiety, is specifically associated with poorer threat extinction learning and retention, as well as overgeneralisation. Under periods of estimation and expected uncertainty, where the parameters of uncertainty are being learned or have been learned, such as threat acquisition training and avoidance learning, the findings are mixed for IU. These findings provide evidence that individual differences in IU play a significant role in maintaining learned fear and anxiety, particularly under volatile environments. Recommendations for future research are outlined, with discussion focusing on how parameters of uncertainty can be better defined to capture how IU is involved in the maintenance of learned fear and anxiety. Such work will be crucial for understanding the role of IU in neurobiological models of uncertainty-based maintenance of fear and anxiety and inform translational work aiming to improve the diagnosis and treatment of relevant psychopathology. •We provide a review on the role of IU in classical threat conditioning procedures.•Parameters of uncertainty determine the association of IU with learning indexes.•IU is related to specific learning indexes under periods of unexpected uncertainty.•These observations can guide future research on IU and threat conditioning.